Mispricing Narratives after Social Unrest - Bocar A. Ba; Abdoulaye Ndiaye; Roman G. Rivera; Alexander Whitefield (CESifo GmbH, 2024)
We study how negative sentiment around an industry impacts beliefs and behaviors, focusing on demands for racial justice after the murder of George Floyd and the salience of the “defund the police” movement. We assess stakeholder beliefs on the impact of protests on the stock prices of police-affiliated firms. In our survey experiment, laypeople and finance professionals predicted more negative stock price outcomes when they lacked details on the products supplied by such firms. Exposure to narratives about the context of the protests further reduced the prediction accuracy of these groups. In contrast, product information improved the prediction accuracy of respondents. Turning to real-life behavior, we find that mutual funds exposed to protests were 20% less likely to hold police stocks, after the protests, than funds in areas without protests. Political support for maintaining police funding, though in the majority, declined by 4.3 percentage points in protest areas. The salience of the “defund the police” narrative led to significant overreactions in both financial predictions and real-life behaviour.
Keywords: D72; D74; D83; G41; 330; narratives; reasoning; surveys; financial prediction; social movements